Raman study of Yuan Qinghua porcelain: the highlighting of dendritic CoFe2O4 crystals in blue decorations. (21st September 2016) - Wang, Tian; Zhu, Tiequan; Brunet, Magali; Deshayes, Christophe; Sciau, Philippe
Abstract : Raman spectroscopy and scanning electron microscopy equipped with energy dispersive spectrometer (SEM‐EDS) were used to analyze the decors of the Yuan blue and white porcelains (Qinghua porcelains). SEM‐EDS carried out on the dark spots of the blue decors revealed the presence of dendritic crystals of a mix cobalt iron oxide. The Raman spectra of these crystals are close to the standard spectrum of cobalt ferrite (CoFe2 O4 ). Comparing the Fe/Co ratios obtained by EDS to the corresponding Raman spectra, we have identified two main types of spinel crystals: one type richer in iron and another type richer in cobalt. Both types of spinel cause the blackening of the blue decors. It is the first time that spinel crystals with a composition close to cobalt ferrite were observed as the main constituent of the dark spots in blue decors of Qinghua porcelains. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : For Yuan productions, the blue decors present dark spots contrasting finely with the blue parts. It is currently believed that the dark spots are attributed to magnetite (Fe3 O4 ). Nevertheless, in our work for the first time dendritic cobalt ferrite (CoFe2 O4 ) crystals were observed by scanning electron microscopy and Raman spectroscopy as the main constituent of the dark spots. Through investigations, there were two types of populations existed in these spinel crystals—spinel richer in iron (Co3 −  x Fe x O4, x  > 2) and spinel richer in cobalt (Co3 −  x Fe x O4, x  < 2). Both cause the blackening of the blue decors.